2010
DOI: 10.1111/j.1399-0012.2009.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical training effects in renal transplant recipients

Abstract: This study suggests that an appropriate dose of physical training is a useful, safe and non-pharmacologic contribution to RTR treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
0
22
2
Order By: Relevance
“…18.1 [ 74 , 75 ]. A small study of prescribed exercise in renal transplant recipients demonstrated improved cardiorespiratory parameters, such as V O 2 max, but no difference in any of the measured biochemical parameters [ 76 ]. Of note in this study was a statistically signifi cant decrease in the infl ammatory cytokine IL-6 after 30 sessions of exercise training.…”
Section: Diet and Exercisementioning
confidence: 90%
“…18.1 [ 74 , 75 ]. A small study of prescribed exercise in renal transplant recipients demonstrated improved cardiorespiratory parameters, such as V O 2 max, but no difference in any of the measured biochemical parameters [ 76 ]. Of note in this study was a statistically signifi cant decrease in the infl ammatory cytokine IL-6 after 30 sessions of exercise training.…”
Section: Diet and Exercisementioning
confidence: 90%
“…In a high-intensity interval training study (3-weekly sessions of 15× 1-minute intervals at 90% HR peak ) in renal transplant patients large reductions in IL-6 were reported after 10 weeks (before 2.8 ± 0.6 versus after 1.7 ± 0.5 pg/mL) [109]. Although this study had no control group this may represent a training load required to stimulate a significant adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is likely that their reported maximal exercise values are considerably below their own potential maximum pre-RTx, as athletic populations typically demonstrate much higherVo 2peak than the average population, although this obviously cannot be tested in these RTx recipients (237). Studies in RTx patients with mean ages of 40 to 50 years also demonstrated a lowVo 2peak relative to controls or predicted values (11,248,265). Petersen et al found aVo 2peak of 27.0 ml.kg −1 .min −1 in nine RTx aged 41 years (254, 317), which was 76% of the matched control group.…”
Section: Nrmentioning
confidence: 93%